Integrating Earth Alms Values: A New Approach to Teaching Social Sciences - Desyani, Desyani; Yadegar, Roya (Journal of Social Knowledge Education (JSKE), 2024)
Purpose of the study: Describe the values and use of local wisdom from the Sedekah Bumi tradition as a source of social science learning. Methodology: This research uses a qualitative approach with descriptive research type, data collection techniques using observation, interviews and documentation. Meanwhile, the technical data analysis used is the Miles, Huberman and Saldana interactive model. Validity of data using triangulation techniques and sources. Main Findings: The research findings are: (1) The Earth Alms tradition in Curahnongko Village includes religious practices such as offerings and communal prayers. (2) It promotes mutual cooperation through community activities like building mountains and organizing processions. (3) It emphasizes environmental care by protecting banana trees, avoiding damage to roadside plants, and cleaning up after events. (4) It aligns with social studies curriculum for various grades: Class VII focuses on Social Interaction and Social Institutions; Class VIII on the impact of social interaction on social and national life; and Class IX on Indonesia's history from independence to the reform period. Novelty/Originality of this study: This research produces innovation in integrating local wisdom values from the Sedekah Bumi tradition into social studies learning in junior high schools, creating an educational approach that is more contextual and relevant for students.